Hygienic-sanitary quality of donated human milk in terms of the donor profile and pumping site - Souza, Ana Carolina de Prima; Rocha, Ana Carolina Lavio; Castro, Lucíola Sant'Anna de; Camargo, Bárbara Tideman Sartorio; Fogliano, Rosana Rodrigues Figueira; Tsunemi, Miriam Harumi [UNESP]; Coca, Kelly Pereira (FapUNIFESP (SciELO), 2025)
OBJECTIVE: To analyze the factors associated with the hygienic-sanitary quality of donated human milk in terms of the donor profile and pumping site. METHOD: Cross-sectional study with retrospective data collection of records of human milk samples donated to a Human Milk Bank in São Paulo, Brazil, from 2014 to 2019. Characteristics of human milk donors, pumping site, and hygienic-sanitary quality were analyzed based on the Standards of the Brazilian Human Milk Bank Network. RESULTS: In the hygienic-sanitary assessment, a greater presence of contamination, high acidity, and microbiological alteration were found when human milk was pumped at home and when it was donated mature. The human milk from non-exclusive donors, especially those > 30 years old, presented greater microbiological contamination and higher acidity when compared to that from exclusive donors (p < 0.05). CONCLUSION: Hygienic-sanitary quality impairment of donated human milk occurred when the collection was performed at home, especially among non-exclusive donors. Effective guidance and indirect supervision of donors who perform home pumping can contribute to better use of donated human milk.